Alkylation of Nitrogen-Containing Heterocycles via In Situ Sulfonyl Transfer - Panteleev, Jane; Maguire, Robert J.; Kung, Daniel W. (Synlett, 2015)
A convenient synthesis of N-substituted heterocycles from primary and secondary alcohols and N-sulfonyl heterocycles is described. The reaction proceeds through sulfonyl transfer and in situ formation of activated alcohol derivatives. The formation of alkyl sulfonates as transient intermediates mitigates challenges associated with isolation of these reactive species. N-Sulfonyl heteroarenes were found to be stable over prolonged time, and efficiently coupled to a variety of alcohols.
Keywords: pyrazoles; sulfonyl transfer; N-heterocycles; SN2 reaction; alkylation